Muslim common religious practices at the Cape : identification and analysis - Mukadam, Ahmed (University of Cape Town, 2015)
Bibliography: leaves 92-96. === This dissertation examines the side by side existence of Popular Islam, or Muslim Common Religious Practices, with Official Islam in the Cape of today. Our task is thus primarily to identify the popular movement as no systematic documentation in this field has to date been attempted. Almost all approaches in Islamic Studies have concentrated an Official Islam and mostly from theological perspectives. In those works references to particular common beliefs and practices have been made and sometimes suggestively. Comparatively, however, much more, and perhaps methodologically not enough, has been done in Christian studies under the headings of Popular Religion, African Christology and very importantly, African Indigenous Church movements. The academic study of Islam, however, is still a relative novelty in South Africa and we suspect that the area of research into the popular movement may not gather momentum as rapidly as studies on the official movement. This apathy towards this "invisible institution" is attributable to the marginality it receives as a religious response.